Dietary spermidine for lowering high blood pressure. Issue 4 (3rd April 2017) - Eisenberg, Tobias; Abdellatif, Mahmoud; Zimmermann, Andreas; Schroeder, Sabrina; Pendl, Tobias; Harger, Alexandra; Stekovic, Slaven; Schipke, Julia; Magnes, Christoph; Schmidt, Albrecht; Ruckenstuhl, Christoph; Dammbrueck, Christopher; et al.
ABSTRACT: Loss of cardiac macroautophagy/autophagy impairs heart function, and evidence accumulates that an increased autophagic flux may protect against cardiovascular disease. We therefore tested the protective capacity of the natural autophagy inducer spermidine in animal models of aging and hypertension, which both represent major risk factors for the development of cardiovascular disease. Dietary spermidine elicits cardioprotective effects in aged mice through enhancing cardiac autophagy and mitophagy. In salt-sensitive rats, spermidine supplementation also delays the development of hypertensive heart disease, coinciding with reduced arterial blood pressure. The high blood pressure-lowering effect likely results from improved global arginine bioavailability and protection from hypertension-associated renal damage. The polyamine spermidine is naturally present in human diets, though to a varying amount depending on food type and preparation. In humans, high dietary spermidine intake correlates with reduced blood pressure and decreased risk of cardiovascular disease and related death. Altogether, spermidine represents a cardio- and vascular-protective autophagy inducer that can be readily integrated in common diets.